Financial Information Disclosure of Political Parties (Case Study of Political Parties at the Regional Leadership Council Level in East Nusa Tenggara Province) - Johanis Kuahaty; Petrus Kase; Laurensius Petrus Sayrani (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2025)
Financial information disclosure by political parties is a key requirement for democratic accountability, particularly at the subnational level where parties receive public funding but face limited public scrutiny. Although Indonesia has established a formal legal framework for party finance transparency, disclosure practices at the Regional Leadership Council (DPD) level remain weak. Existing studies primarily emphasize national-level compliance and overlook the organizational and socio-political dynamics influencing transparency in regional party structures. This study employs a descriptive qualitative case study approach to analyze financial information disclosure by political parties in East Nusa Tenggara Province. Data were collected through in-depth interviews with selected DPD officials, document analysis, and participatory observation, and analyzed using thematic analysis. The findings reveal that transparency is supported by regulatory provisions, individual cadre awareness, external oversight pressure, and reputational considerations, while being constrained by the absence of technical disclosure guidelines, elite dominance, patrimonial political culture, weak public demand, limited institutional capacity, and lack of enforceable sanctions. The study demonstrates that formal regulations alone are insufficient, highlighting the need for technical guidelines, internal capacity strengthening, and enhanced civil society oversight to institutionalize meaningful financial transparency.